Level of viral suppression and the cascade of HIV care in a South African semi-urban setting in 2012. (24th August 2016) - Jean, Kévin; Puren, Adrian; Cutler, Ewaldé; Singh, Beverley; Bouscaillou, Julie; Rain-Taljaard, Reathe; Taljaard, Dirk; Gouws, Eleanor; Lissouba, Pascale; Lewis, David A.; Peytavin, Gilles; Auvert, Bertran
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: In 2012, 7 years after the introduction of antiretroviral treatment (ART) in the South African township of Orange Farm, we measured the proportion of HIV-positive people who were virally suppressed, especially among high-risk groups (women 18–29 years and men 25–34 years). Design: A community-based cross-sectional representative survey was conducted among 3293 men and 3473 women. Methods: Study procedures included a face-to-face interview and collection of blood samples that were tested for HIV, 11 antiretroviral drugs and HIV-viral load. Results: HIV prevalence was 17.0% [95% confidence interval: 15.7–18.3%] among men and 30.1% [28.5–31.6%] among women. Overall, 59.1% [57.4–60.8%] of men and 79.5% [78.2–80.9%] of women had previously been tested for HIV. When controlling for age, circumcised men were more likely to have been tested compared with uncircumcised men (66.1 vs 53.6%; P  < 0.001). Among HIV+, 21.0% [17.7–24.6%] of men and 30.5% [27.7–33.3%] of women tested positive for one or more antiretroviral drugs. Using basic calculations, we estimated that, between 2005 and 2012, ART programs prevented between 46 and 63% of AIDS-related deaths in the community. Among antiretroviral-positive, 91.9% [88.7–94.3%] had viral suppression (viral load <400 copies/ml). The proportion of viral suppression among HIV+ was 27.0% [24.3–29.9%] among women and 17.5% [14.4–20.9%] among men. These proportions were lower among the high-risk groups: 15.6% [12.1–19.7%] among women and 8.4% [5.0–13.1%] among men. Conclusion: In Orange Farm, between 2005 and 2012, ART programs were suboptimal and, among those living with HIV, the proportion with viral suppression was still low, especially among the young age groups. However, our study showed that, in reality, antiretroviral drugs are highly effective in viral suppression at an individual level.